Simultaneous Presentation of Multiple Documents and Text-Highlighting: Online Integrative Processes and Offline Integrated Understanding. (4th March 2021) - Leroy, Caroline; Gerjets, Peter; Oestermeier, Uwe; Kammerer, Yvonne
ABSTRACT: This study examined the effect of the reading environment, i.e., documents presentation and possibility of text-highlighting, on readers' integrated understanding, as well as the interplay between the reading environment and overt reading processes (i.e., online integrative processes) in forming intertextual connections. University students ( N = 126) read six partly conflicting documents presented on a large multi-touch table, which were presented simultaneously or sequentially, with or without the possibility of text-highlighting. The simultaneous presentation yielded better integrated understanding, with this effect being fully mediated by an increased likelihood to spatially organize documents during reading. Furthermore, the possibility of text-highlighting also fostered readers' integrated understanding. Additional analyses (sequential presentation only), however, indicated that this was not the case for participants who only infrequently revisited documents. We discuss this complex interplay between the reading environment and readers' online integrative processes in the light of the RESOLV model.